The Effect Chat Feature on Genshin Impact Online Game on ESL Communication Skills - Azizah, Nur; Warni, Silih (research, training and philanthropy institution Natural Aceh, 2024)
Learning English is not only conducted at school but can be conducted through alternative media. These include watching English movies, listening to English songs, and playing online games. Online games do not merely have a negative impact, but they can also positively impact the user. Genshin Impact is an online game that is currently booming. Various features in Genshin Impact allow players to interact with other players by entering Co-Op mode. This research aims to discover whether students are motivated to improve their English communication skills through the chat feature in the online game Genshin Impact. This study employed a descriptive quantitative methodology. The data were then analyzed descriptively to answer the research question. 151 respondents from various schools were selected based on the required criteria. From the result data analysis, students perceive that using the chat feature in Genshin Impact can positively influence students' motivation to improve their English communication skills. The findings also revealed that students agree and strongly agree that online games can increase their motivation to learn English. The results of this study's implications encourage teachers to start thinking about the benefits of games in education.